A note on resistance to Hessian fly (Mayetiola destructor) [Diptera : Cecidomyidae] biotype L in tribe Triticeae - Sharma, H.C.; Foster, J.E.; Ohm, H.W.; Patterson, F.L. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1992)
Forty-one accessions of primitive and wild wheats (Triticum species), 16 accessions of Aegilops species, and 20 accessions or cultivars of Agropyron species were evaluated for the first time for reaction to biotype L of Hessian fly (Mayetiola destructor). Three accessions of Triticum monococcum, 13 accessions of Aegilops species, and 13 accessions or cultivars of Agropyron species were found homogeneously resistant. Antibiosis was operative in some cases but in others there appeared to be physical resistance due to the presence of leaf pubescence or ligule. Pubescence of Triticum boeoticum was not effective in providing resistance.